Triacylglycerol accumulation and oxidative stress in Rhodococcus species: differential effects of pro-oxidants on lipid metabolism - Bequer Urbano, Susana de los Ángeles (2014)
In general, members of Rhodococcus genus are highly resistant to desiccation. Desiccation is a complex process which includes the formation of reactive oxygen species that results in significant damage to cells. In this study, we demonstrate that extremophile actinobacterial strains isolated from diverse environments, mainly belonging to Rhodococcus genus, exhibited high tolerance to the pro-oxidants hydrogen peroxide (H2O2) and methyl viologen (MV). In addition, we investigated the possible interconnections between the responses of the oleaginous Rhodococcus opacus PD630 to oxidative stress and lipid metabolism, since both processes demand a metabolic reorganization of cells. Experiments with metabolic inhibitors showed differential effects of both pro-oxidants on lipid metabolism in PD630 cells. The inhibition of carotenoid biosynthesis by the addition of diphenylamine to the media negatively affected the tolerance of cells to H2O2, but not to MV. The inhibition of triacylglycerol (TAG) biosynthesis and accumulation in PD630 did not affect the tolerance of cells to H2O2 and MV; whereas, the blockage of lipolysis decreased the tolerance of cells to H2O2 (but not MV) under carbon-starvation conditions. Interestingly, the addition of MV to the media (but not H2O2) induced a reduction of TAG accumulation by cells. Resuming, results of this study revealed metabolic connections between lipid metabolism and oxidative stress responses in R. opacus PD630, and probably in other extremophile TAG-accumulating rhodococci